Studi Komparatif Tingkat Pendapatan Antara Usaha Kelapa dan Pinang pada Perkebunan Rakyat Desa Sungai Beras Kabupaten Tanjab Timur - Akhmadi Akhmadi; Etty Siswati; Nurrasyidah Putri (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This type of research is quantitative research that is research using data expressed in numerical form on parts and phenomena and their relationships. This research usually aims to develop and use mathematical models, theories or hypotheses related to natural phenomena. This research is a survey and interview directly to the owners of coconut and areca nut business and records everything that the writer needs in connection with the problem of the writer. In this study using data analysis methods, namely qualitative data analysis. Qualitative data is data in the form of not numbers but with words that can be used to describe, complete and explain and strengthen quantitative data directly in the field. (Sugiyono, 2011: 23). production costs are all costs associated with the goods produced, wherein there are elements of raw material costs, direct labor costs and factory overhead costs. Based on the time period, production can be divided into short-term and long-term. In the short term the company during its production period can add one factor of production while other factors of production are considered constant. This means that some factors of production cannot be added. Whereas in the long run, companies can change or add to all factors of production they use. The initial investment of a coconut plantation business is Rp.37,004,000 which is calculated before the production period of 7 (seven) years and the initial investment of areca nut plantation is Rp.34,750,000 which is calculated before the production period for 4 (four) years, for production costs in one the coconut plantation business year is obtained at Rp.5,600,000 and the production cost of the areca nut business in one year is Rp.108,200,000, the comparison between the coconut plantation business income and the areca nut business revenue is obtained for the income of the coconut plantation business income for one year of Rp. .14,400,000 and the results of areca nut business revenue for one year amounted to Rp. 110,200,000 So, it can be concluded that the biggest income is in the nut business compared to the coconut business.